2016
DOI: 10.1186/s40795-016-0113-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between dietary intake and serum ganglioside concentrations: a cross-sectional study among Malaysian toddlers

Abstract: Background: Gangliosides are a group of sialylglycosphingolipids, widely distributed in body tissues, mainly as components of plasma membranes. They play crucial roles in neurodevelopment, gut maturation, and immune system. Dietary gangliosides have been shown to bring about benefits including cognition and immune support for breastfed infants. There is dearth of studies on dietary gangliosides intake or plasma ganglioside levels for toddlers. Given toddlers are still growing rapidly, a good understanding of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
1
16
3
Order By: Relevance
“…All the GUMPS consumed by these toddlers were based on bovine milk, having a TGA content ranging from 2.80 mg/100 g to as high as 16.10 mg/100 g. This range is consistent with those for other bovine-milk-based GUMPs reported in the literature [27,28,29,30]. The study by Khor et al [14] also reported that GUMPs were the major source of dietary GAs (5.05 ± 56 mg/day, 85%) for Malaysian toddlers. However, a larger proportion (77%) of the Malaysian toddlers consumed GUMPs, compared with only 61% (Table 2) of the Indonesian toddlers.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…All the GUMPS consumed by these toddlers were based on bovine milk, having a TGA content ranging from 2.80 mg/100 g to as high as 16.10 mg/100 g. This range is consistent with those for other bovine-milk-based GUMPs reported in the literature [27,28,29,30]. The study by Khor et al [14] also reported that GUMPs were the major source of dietary GAs (5.05 ± 56 mg/day, 85%) for Malaysian toddlers. However, a larger proportion (77%) of the Malaysian toddlers consumed GUMPs, compared with only 61% (Table 2) of the Indonesian toddlers.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the Indonesian toddlers consumed an average of 6.13 ± 0.56 mg TGA/day ( Table 7). This was not significantly different (p = 0.76) compared to an average of 5.68 ± 0.56 mg TGA/day reported for Malaysian toddlers [14]. Both these intake levels are much lower than those typically measured for exclusively breast-fed infants.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations